2009
DOI: 10.1111/j.1398-9995.2009.02156.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled vs subcutaneous effects of a dual IL‐4/IL‐13 antagonist in a monkey model of asthma

Abstract: Local administration of pitrakinra to the lung is sufficient to inhibit AHR, one of the cardinal features of asthma, indicating the therapeutic potential of inhaled pitrakinra in the treatment of atopic asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 44 publications
(67 reference statements)
0
25
0
1
Order By: Relevance
“…When STAT-6 was reconstituted only in the lung epithelia of IL-13-overexpressing mice AHR and mucus hypersecretion, but not BAL eosinophilia or fibrosis, phenotypes returned implicating the epithelium as a key IL-13 target cell type in the asthmatic phenotype [88]. Cynomolgus monkey testing of the IL-4 mutant pitrakinra demonstrated that local (inhaled) dosing delivered similar effects, of reduced AHR and a trend toward decreased lung eosinophils, as systemic (subcutaneous) dosing [89]. This important study confirmed the notion that neutralization of IL-4 and IL-13 in the lung, rather than the periphery, is important for efficacy against AHR and eosinophilia in models mimicking key aspects of human asthma.…”
Section: Animal Model Datamentioning
confidence: 84%
“…When STAT-6 was reconstituted only in the lung epithelia of IL-13-overexpressing mice AHR and mucus hypersecretion, but not BAL eosinophilia or fibrosis, phenotypes returned implicating the epithelium as a key IL-13 target cell type in the asthmatic phenotype [88]. Cynomolgus monkey testing of the IL-4 mutant pitrakinra demonstrated that local (inhaled) dosing delivered similar effects, of reduced AHR and a trend toward decreased lung eosinophils, as systemic (subcutaneous) dosing [89]. This important study confirmed the notion that neutralization of IL-4 and IL-13 in the lung, rather than the periphery, is important for efficacy against AHR and eosinophilia in models mimicking key aspects of human asthma.…”
Section: Animal Model Datamentioning
confidence: 84%
“…Furthermore, our study revealed that evaluation of circulating IL-13Rα2 concentration and saturation may be useful to understand the kinetics of IL-13 elaboration in injury models and to appropriately time anti-IL-13 interventions. Indeed, several investigators have previously studied the anti-fibrotic efficacy of targeting IL-13-induced signaling, either through targeted delivery of immunotoxins8, disruption of ligand-receptor interactions262728, or by direct IL-13 neutralization, a strategy that is currently yielding promising results in humanized models29, and has advanced to clinical trials in human subjects with severe asthmatic airway disease and other disease driven by IL-1330313233. In our experiments, we used an IL-13 neutralizing IgG during the period of IL-13Rα2 nadir and saturation significantly disrupted the progression of radiation-induced pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has yet to be firmly established in a model of CMV infection, it has been suggested that apoptotic pathways may be directly induced as a result of TLR2 activation. For example, there exists evidence for extrinsic apoptosis, demonstrated by the in vitro exposure of HCMV to syncytiotrophoblasts, which produce TNF-a as a result of TLR2 activation, inducing apoptosis in neighboring cells (Tomkinson et al, 2010).…”
Section: Integration Of Innate Immunity and Cell Deathmentioning
confidence: 99%